Interferência e controle de milho voluntário resistente ao glifosato na cultura da soja - Piasecki, Cristiano (2015)
A weed is any plant that grows where it is not wanted. Thus, any plant can be considered weed if its presence is not convenient. Since the introduction of Roundup Ready ® technology in soybean and corn, it was increased the frequency of soybean crops in the presence of volunteer RR® F2 corn plants. Volunteer plants are originated from crop losses, with individual grains, or seeds attached to several pieces o f the rachis, giving individual plants or clumps. Volunteer corn competes for environmental resources causing loss of yield and changes in soybean morphophysiology. The objective of this study was to quantify the losses in grain yield, and morphological and physiological changes in soybean due to the populations interference and relative times of emergency of individual plants and clumps of volunteer corn RR ®F2. There were also studied pre-emergent herbicide in the control of individual plants and clumps o f volunteer corn RR ®F2. The results demonstrated that even in a population of less than 1 m -2 volunteer corn RR®F2 originated from individual plants and clumps significantly it reduces the yield of soybeans, justifying its control. Volunteer corn clumps cause more severe losses in soybeans yield. The faster the corn emergence in comparison to the soy , the bigger the loss in yield of soybeans is. The production of hydrogen peroxide (H2O2) in soybeans was lower due to increased competition. The competition of volunteer corn populations did not significantly change the enzyme ascorbate dismutase (APX), catalase (CAT) and superoxide dismutase (SOD). Herbicides chlorimuron + sulfometuron, diclosulam and imazapic + imazapyr are efficient in the pre-emergence control of individual plants of volunteer corn, showing superior control to 80%.